2011
DOI: 10.1111/j.1365-2141.2011.08784.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug induced immune haemolytic anaemia in the Berlin Case‐Control Surveillance Study

Abstract: Summary Drug‐induced immune haemolytic anaemia is a rare but serious condition. This study investigated the possibility of drug aetiology of immune haemolytic anaemia (IHA) in 134 patients with new onset of IHA who were identified in the Berlin Case‐Control Surveillance Study between 2000 and 2009. Single drugs related to IHA in three or more patients and assessed more than once as a certain or probable cause of IHA in a standardized causality assessment included diclofenac, fludarabine, oxaliplatin, ceftriaxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 34 publications
1
78
1
6
Order By: Relevance
“…Although reactions are variable, DIIHA can be life-threatening (2). The estimated incidence of this disorder is approximately 1 per 1 million patients per year, although this is likely an underestimate, as many cases are unappreciated or misdiagnosed, often as warm-type autoimmune hemolytic anemia (AIHA).…”
Section: Introductionmentioning
confidence: 99%
“…Although reactions are variable, DIIHA can be life-threatening (2). The estimated incidence of this disorder is approximately 1 per 1 million patients per year, although this is likely an underestimate, as many cases are unappreciated or misdiagnosed, often as warm-type autoimmune hemolytic anemia (AIHA).…”
Section: Introductionmentioning
confidence: 99%
“…The above report`s finding of increased hemolysis is a consistent finding but not the osmofragility of present study. Garbe et al 2011 (28) has also reported atorvastatin induced hemolysis in human beings.CoQ10 is synthesized by similar HMG Co A pathway of cholesterol. Mevalonate is the precursor of cholesterol as well as CoQ10.…”
Section: Discussionmentioning
confidence: 94%
“…Corticosteroids can be considered if the haemolysis persists 21. From the limited literature available, a short course of prednisolone (2–4 mg/kg) may reduce the duration of anaemia 18 22. There is little evidence surrounding the use of immunoglobulin therapy and rituximab in these patients as the cold antibody-induced autoimmune haemolysis is normally self-limiting.…”
Section: Further Resultsmentioning
confidence: 99%